Real exchange rate overshooting in real business cycle model: An empirical evidence from India - Patrick Minford; Soubarna Pal (Cardiff University, Cardiff Business School, 2008)
The objective of this paper is to establish the ability of a Real Business Cycle (RBC) model to account for the behaviour of the real exchange rate, using Indian data (1966-1997). We calibrate the dynamic general equilibrium open economy model (Minford, Sofat 2004) based on optimising decisions of rational agents, using annual data for India. The first order conditions from the households' and firms' optimisation problem are used to derive the behavioural equations of the model. The interaction with the rest of the world comes in the form of uncovered real interest rate parity and current account both of which are explicitly micro- founded. The paper discusses the simulation results of 1 percent per annum productivity growth shock, which shows that the real exchange rate appreciates and then goes back to a new equilibrium (lower than the previous one), producing a business cycle. Thus the behaviour of the real exchange rate may be explicable within the RBC context. Finally we test our model and evaluate statistically whether our calibrated model is seriously consistent with the real exchange rate data, using bootstrapping procedure. We bootstrap our model to generate pseudo real exchange rate series and find that the ARIMA parameters estimated for the actual real exchange rate data lie within the 95% confidence limits.
Keywords: 330; Kaufkraftparität; Real Business Cycle; Offene Volkswirtschaft; Indien